2008
DOI: 10.1016/j.jtcvs.2008.02.087
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular assist device as bridge to transplantation does not adversely affect one-year heart transplantation survival

Abstract: When used as a bridge to transplantation, left ventricular assist devices do not compromise 1-year survival after cardiac transplantation. Of the patients who die after transplantation, patients bridged with left ventricular assist devices are at higher risk for death within 30 days of transplant. These data suggest that left ventricular assist devices as a bridge to transplantation should be considered for appropriately selected patients awaiting cardiac transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 6 publications
3
25
0
1
Order By: Relevance
“…Studies in the past that use single-center CFVAD data and UNOS data from predominantly the pulsatile device era have reported decreased post-transplantation survival in patients with device complications, which is similar to our finding of marginally reduced posttransplantation survival in CFVAD patients with device complications [14][15][16]. Because patients with device complications and patients not eligible for CFVAD are at higher risk of waiting list mortality, prioritizing them for transplantation by quantifying their risk of waiting list and post-transplantation survival rather than allowing lower risk patients a 30-day grace period to be at higher priority will allow more judicious organ allocation and increase the reach of transplantation therapy to more patients.…”
Section: Commentsupporting
confidence: 89%
“…Studies in the past that use single-center CFVAD data and UNOS data from predominantly the pulsatile device era have reported decreased post-transplantation survival in patients with device complications, which is similar to our finding of marginally reduced posttransplantation survival in CFVAD patients with device complications [14][15][16]. Because patients with device complications and patients not eligible for CFVAD are at higher risk of waiting list mortality, prioritizing them for transplantation by quantifying their risk of waiting list and post-transplantation survival rather than allowing lower risk patients a 30-day grace period to be at higher priority will allow more judicious organ allocation and increase the reach of transplantation therapy to more patients.…”
Section: Commentsupporting
confidence: 89%
“…Left ventricular assist devices are used for endstage heart failure patients as destination therapy, as bridge to transplant, as bridge to candidacy, or as bridge to recovery. [5][6][7] Teuteberg and associates highlighted that the possibility of a heart transplant during LVAD support changes continually over time. In an analysis of 2816 patients enrolled in the Interagency Registry for Mechanically Assisted Circulatory Support, Teuteberg and associates showed that 43.5% of patients who initially received the device with bridge to transplant intent were no longer listed as candidates for cardiac transplant 2 years after LVAD implant.…”
Section: Discussionmentioning
confidence: 99%
“…In case of inability of the donor heart to cope hemodynamically in the orthotopic position, we planned to use a shortterm ventricular assist device while awaiting another available donor organ. 7 We also considered the option of excising the native heart and leaving the donor heart in the original heterotopic position by anastomosing the donor pulmonary artery to the native pulmonary artery and closing the aortic root, pulmo- nary root, mitral annulus and tricuspid annulus of the native heart. 8 However, this would have involved use of a Dacron graft and would leave a space within the pericardial cavity that would be subject to organizing fibrosis and would disallow future retransplantation.…”
Section: Discussionmentioning
confidence: 99%